Edukasi pembuatan simplisia sebagai bahan baku obat herbal pada siswi MA Darunnajah Duman - Aulia, Dia Ul; Khairatun, Laziza Iklima; Hidayati, Agriana Rosmalina (Universitas Mataram, 2024)
Plants can be used as medicine (herbs) and used directly or processed into simplisia. Knowledge about plants used as medicine and how to process them among students is still limited. The purpose of this activity is to provide education to students about making simplisia and its benefits in traditional medicine. This education can increase the knowledge and skills of female students in processing herbal plants. The method used was a combination of lectures, discussions, and practical demonstrations of the steps of making simplisia using plants in the MA Darunnajah school. The result of the activity can be seen through the students' improved understanding of herbal plants, from sampling to storing procedures. In conclusion, the student's knowledge about the efficacy of various plants in the school environment increased, and they had good skills in processing fresh plants into simplisia.